2009
DOI: 10.1107/s1600536809015864
|View full text |Cite
|
Sign up to set email alerts
|

1-(2-Chloroacetyl)-3-methyl-2,6-bis(3,4,5-trimethoxyphenyl)piperidine-4-one

Abstract: In the crystal structure of the title compound, C26H32ClNO8, the piperidine ring is in a twist-chair conformation, with puckering parameters Q = 0.655 (4) Å, θ = 93.1 (1) and ϕ = 254.4 (3)°. The ortho C atoms of the piperidine ring deviate from the plane defined by the remaining ring atoms by 0.380 (3) and −0.250 (3) Å.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…The bond lengths and angles are in agreement with those in related structures (El-Hiti et al, 2014;Al-Salahi et al, 2012;Utayeva et al, 2013;Priya et al, 2011;Lakshminarayana et al, 2009Lakshminarayana et al, , 2022Sreenatha et al, 2018aSreenatha et al, ,b, 2020Sreenatha et al, , 2022.…”
Section: Structural Commentarysupporting
confidence: 87%
“…The bond lengths and angles are in agreement with those in related structures (El-Hiti et al, 2014;Al-Salahi et al, 2012;Utayeva et al, 2013;Priya et al, 2011;Lakshminarayana et al, 2009Lakshminarayana et al, , 2022Sreenatha et al, 2018aSreenatha et al, ,b, 2020Sreenatha et al, , 2022.…”
Section: Structural Commentarysupporting
confidence: 87%
“…A search of the Cambridge Crystallographic Database (CSD version 5.39, updates February 2018; Groom et al, 2016) revealed three examples of organic compounds having piperdine-4-one as the central unit, namely 1-acryloyl-3-methyl-2,6bis(3,4,5-trimethoxyphenyl)piperidine-4-one , N-nitroso-2,6-di(3,4,5-trimethoxyphenyl)-3,5-dimethylpiperidin-4-one (Kumaran, et al, 1999) and 1-(2chloroacetyl)-3-methyl-2,6-bis(3,4,5-trimethoxyphenyl)piper-idine-4-one (Lakshminarayana et al, 2009). A study of the supramolecular features of these compounds revealed that the crystal lattices are stabilized mainly by C-HÁ Á ÁO intermolecular interactions, forming two-dimensional networks.…”
Section: Database Surveymentioning
confidence: 99%